The pollution flashover on high voltage insulators - Gencoglu, Muhsin Tunay; Cebeci, Mehmet (Elsevier Science Sa, 2008)
The pollution flashover, observed on insulators used in high voltage transmission. is one of the most important problems for power transmission. It is a very complex problem due to several factors such as the modeling difficulties of complex shapes of the insulators. different pollution density at different regions, non-homogeneous pollution distribution on the insulator surface and unknown effect of humidity on the pollution. In the literature, some static and dynamic models were developed by making some assumptions and omissions to predict the flashover voltages of polluted insulators. In this study, historical development of insulator modeling was investigated and a dynamic arc model was proposed. For this purpose, scaled shape of a concerned insulator was firstly partitioned into triangular elements. then finite element method (FEM) was implemented and finally potential distribution on the insulator Surface, variation of pollution resistance and flashover voltage were determined. The computed flashover voltage values of the selected string insulator have been compared to results from other research. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: insulator; pollution flashover; pollution resistance; flashover voltage; insulator equivalent model